Caracterización de la actividad Enzimática de la B-Galactosidasa aislada de un cultivo líquido de Pleurotus ostreatus a base de suero de leche - Plasencia Cerna, Olga Danitza (2019)
ABSTRACT The aim of the present research was characterize the enzymatic activity of ß-galactosidase isolated from a liquid culture of Pleurotus ostreatus based on whey. For this, samples of mycelium of P. ostreatus were cultivated in agar whey and incubated for 20-24 days. Fragments of 1 cm2 of the mycelial growth were transferred to culture media containing whey broth, leaving in growth for 21 days. The liquid cultures were filtered to obtain the crude extract, from which the enzymatic activity, the concentration of enzyme, the effect of pH, temperature, enzyme, substrate ortho-nitrophenyl-β-galactopyranoside (ONPG) and the incubation time were determined; being found that, the crude extract of ß-galactosidase presents an enzymatic activity of 0.394 U/mL, a protein concentration of 0.8545 mg/mL and a specific activity of 0.461 U/mg. The optimal pH and temperature values of the enzyme in the soluble state were at pH 3 and at 35 °C. To calculate the Vmax and Km values of the β-galactosidase, the Lineweaver-Burk kinetic model was graphed where the values were 0,0262 μmol/min and 16,11 mM, respectively. The results revealed that when the enzymatic reaction (enzyme-substrate) is carried out, the increase in the concentration of the product is observed until the reaction ends or reaches its equilibrium point at 30 minutes.